Effects of Bi0.5Na0.5TiO3 dopant on microstructure and thermoelectric properties of NaxCoO2 ceramics - Suwapitcha Buntham (2018)
Copyright © 2015 American Scientific PublishersAll rights reserved. Bi0.5Na0.5TiO3-doped NaxCoO2 ceramics with varied doping concentration of 0, 0.01, 0.03, 0.05 and 0.07 mol fraction were prepared by conventional solid state reaction method. The firing condition used was 950 °C for 8 h. X-ray diffraction pattern results showed that all produced ceramics were single phase with a hexagonal structure. Due to the substitution of BNT inside NaxCoO2 lattice, there was a slight shift of X-ray diffraction pattern to the left which indicated the lattice expansion. The scanning electron micrographs of ceramics indicated that small amount of BNT addition could eliminate pore and improved densification. A small amount of undissolved BNT was also present in NaxCoO2 matrix and dispersed at grain boundaries causing a decrease in grain size of the ceramic. The electrical conductivity and Seebeck coefficient of ceramics showed that all samples possessed metallic conduction behavior. However, BNT addition caused a reduction of electrical conductivity, Seebeck coefficient and power factor of NaxCoO2 ceramics.